2003
DOI: 10.1515/reveh.2003.18.3.203
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Toxicology and Health Effects Associated with Dinitrotoluene Exposure

Abstract: Dinitrotoluenes (DNTs) are nitroaromatic compounds appearing as pale yellow crystalline solids at room temperature. Dinitrotoluenes exist as a mixture of 2 to 6 isomers, with 2,4-DNT, and 2,6-DNT being the most significant. About 500 persons are estimated to be potentially exposed yearly to 2,4-DNT and 2,6-DNT during the production of munitions and explosives. The main route of human exposure at ammunition facilities is inhalation, but dermal contact and inadvertent ingestion can also be substantial. In factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Many nitroaromatic compounds are environmental pollutants or drugs, causing a number of toxic effects on the hematopoietic, cardiovascular, nervous, or reproductive systems (27,29,30,49,50). A major mechanism for the cytotoxicity is believed to involve reductive activation by cellular enzymes with subsequent redox cycling, provoking oxidative stress, a feature shared with various cytotoxic quinones.…”
Section: Discussionmentioning
confidence: 99%
“…Many nitroaromatic compounds are environmental pollutants or drugs, causing a number of toxic effects on the hematopoietic, cardiovascular, nervous, or reproductive systems (27,29,30,49,50). A major mechanism for the cytotoxicity is believed to involve reductive activation by cellular enzymes with subsequent redox cycling, provoking oxidative stress, a feature shared with various cytotoxic quinones.…”
Section: Discussionmentioning
confidence: 99%
“…Toxicity of these compounds to humans and animals has been documented (Tchounwou et al, 2003;Karnjanapiboonwong et al, 2009;Xu and Jing, 2012). DNT isomers are known to cause cancer, to lower sperm number and to reduce fertility in laboratory animals (Rickert et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…To date, evidence from animal studies as well as from epidemiological studies particularly points to a potential aetiological role of DNT exposure on renal and urothelial cancer; for a summary of the epidemiological findings, please see Seidler et al 9 Brüning et al 4–6 found increased renal cell carcinoma risks as well as toxic nephropathy with proximal tubular damage in DNT-exposed underground mining workers in the Mansfield copper mining industry; however, numbers were low. In the mining industry as well as in ammunition facilities,10 there are two main routes of occupational DNT exposures: by inhalation of explosion fumes and by direct skin contact during handling of DNT-containing explosive sticks.…”
Section: Introductionmentioning
confidence: 99%